Acute exacerbations of chronic obstructive pulmonary disease with low serum procalcitonin values do not benefit from antibiotic treatment: a prospective randomized controlled trial. (July 2016) - Wang, Jin-Xiang; Zhang, Shu-Ming; Li, Xiao-Hui; Zhang, Yao; Xu, Zhen-Yang; Cao, Bin
Highlights: Most patients with acute exacerbations of chronic obstructive pulmonary disease have low procalcitonin (PCT) values. Antibiotic therapy was no better than placebo in patients with PCT <0.1 ng/ml. Age ≥75 years was a predictive factor for requiring antibiotic therapy in patients with PCT <0.1 ng/ml. Summary: Objective: The majority of patients with acute exacerbations of chronic obstructive pulmonary disease (AECOPD) have low serum procalcitonin (PCT) values. The aim of this study was to determine whether these patients may benefit from antibiotic treatment. Methods: A total of 457 patients with AECOPD were screened; 194 patients with AECOPD and PCT <0.1 ng/ml were assigned randomly to an antibiotic group or a control group. In the per-protocol (PP) population, the antibiotic group subjects were required to have used antibiotics for at least 3 days, and the control group subjects were required not to have used antibiotics within the 10 days after admission. The intention-to-treat (ITT) population was defined as the patients who were randomized. The primary outcome was the treatment success rate on day 10 after admission. Secondary outcomes were symptoms assessed on a visual analog scale (VAS), length of hospitalization, mortality, exacerbation rate, and re-hospitalization within 30 days of follow-up (study registered at chictr.org.cn: ChiCTR-TRC-14004726). Results: 95 patients in the antibiotic group and 96 patients in the control group completed the study. In the ITT population, the overall treatment success rate in the control group (95.8%) was similar to that in the antibiotic group (93.7%), with no significant difference ( p  = 0.732). Five patients in the antibiotic group died, either in hospital or within 30 days of discharge. In the control group, two died within 30 days of discharge. Antibiotic use in the control group was 17.7% (17/96), and age ≥75 years was a predictive risk factor for requiring antibiotic therapy in the control group (odds ratio 4.055, 95% confidence interval 1.297–12.678; p  = 0.012). According to the PP analysis, the treatment success rate on day 10 after admission was 98.7% (78/79) in the control group and 93.7% (89/95) in the antibiotic group, also with no significant difference ( p  = 0.193). No secondary outcome was significantly different between the two groups. Conclusion: Antibiotic treatment is no better than placebo in AECOPD with a PCT level <0.1 ng/ml.